2012
DOI: 10.1128/jvi.00253-12
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interaction between Vaccinia Virus Proteins A33 and B5 Is Detrimental to Infectious Extracellular Enveloped Virion Production

Abstract: Two mechanisms exist for the incorporation of B5 into extracellular virions, one of which is dependent on A33. In the companion to this paper (W. M. Chan and B. M. Ward, J. Virol. 86:8210 -8220, 2012), we show that the lumenal domain of A33 is sufficient for interaction with the coiled-coil domain of B5 and capable of directing B5-green fluorescent protein (GFP) into extracellular virions. Here, we have created a panel of charge-to-alanine mutations in the lumenal domain of A33 to map the B5 interaction site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…We also found it interesting that coimmunoprecipitation of cells infected with vA34 1-130 -V5 precipitated more B5 than that of cells infected with vA34R-V5. An identical result was reported for certain charge-to-alanine mutations in A33 (58). The mutants also resulted in a small-plaque phenotype.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We also found it interesting that coimmunoprecipitation of cells infected with vA34 1-130 -V5 precipitated more B5 than that of cells infected with vA34R-V5. An identical result was reported for certain charge-to-alanine mutations in A33 (58). The mutants also resulted in a small-plaque phenotype.…”
Section: Discussionsupporting
confidence: 83%
“…The mutants also resulted in a small-plaque phenotype. Further analysis determined that as a result of this stronger interaction, A33 and B5 exist as a detectable complex on the surface of EV and resulted in a reduction in the ability of EV to bind cells (58). It has also been reported that A34 and B5 are present as a complex on the surface of EV during infection (46), and the addition of glycosaminoglycans (GAGs) resulted in a reduction in complex formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that EEV lacking F13 do not exhibit a defect in their ability to bind cells. It has been shown that the presence of A33 and B5 on EEV is required for efficient binding to cells (43,44). Furthermore, the deletion of A34 greatly reduces incorporation of B5 into the EV membrane and drastically reduces infectivity (45,46).…”
Section: Resultsmentioning
confidence: 99%
“…As this interaction is dependent on the coiled-coiled domain being anchored to a membrane, its role in adhesion across the viral envelope membranes is unclear and may represent an independent role for A33 in incorporation of B5 into the envelope, or vice versa [63], [64], [65]. Intriguingly, mutations that increase B5–A33 adhesion result in reduced binding of EEV to host cells suggesting a cis interaction in the membrane between these proteins and raising the possibility that A33 might mask and/or regulate the availability of the adjacent SCR4 [66]. Further characterisation of the nature of these interactions may clarify how adhesion between the outer viral membranes is achieved and regulated.…”
Section: Discussionmentioning
confidence: 99%